Estudo de enzimas digestivas, crescimento e composição centesimal de filés de juvenis de jundiá (Rhamdia quelen) alimentados com diferentes fontes protéicas - Lazzari, Rafael (2005)
This study was aimed at evaluating the growth, fillet composition and digestive enzyme activity of jundiá (Rhamdia quelen, Heptapteridae) juveniles fed different protein sources for 90 days. Five hundred forty fish (initial weight=15.00±0.62g, total length=11,98±0,35cm) were distributed at random in 18 cages of 280L (30 fish/cage) in a water closed system, with controlled temperature. Water quality (total ammonia, nitrite, alkalinity, pH, dissolved oxygen) was checked daily, being in agreement with the appropriate conditions for the species. There were six treatments (with 3 replicates): MBMY (meat and bone meal + yeast), SY (soybean meal + yeast), S (only soybean meal), MBMS (meat and bone meal + soybean meal), FMY (fish meal + yeast) and FMS (fish meal + soybean meal). Growth measurements and data collection were made every 30 days. Performance was evaluated by weight, total and standard length, weight gain, survival, condition factor, specific growth rate, protein efficiency ratio, total biomass, dressing carcass, feed conversion ratio, voluntary feed intake were considered. Protein and fat deposition in the fillet were calculated. Acidic protease, amylase, trypsin and chymotrypsin activities were verified. Best performance was observed in fish fed the animal protein sources (meat and bone meal and fish) with soybean meal. Fat and protein deposition in the fillet was higher (P<0.05) in these treatments (MBMS e FMS). Lower survival was observed in fish fed fish meal plus soybean meal diet (92.86%). However these fish presented better protein efficiency ratio (1.53). Jundiás fed the diet containing only soybean meal (S) as the protein source had growth.reduction. Amilase and acidic protease activities were variable among the treatments. Trypsin activity was higher in fish fed animal protein sources, and the treatments SY and S suffered enzyme inhibition (P<0.0001). The same tendency was observed for chymotrypsin, where fish fed diets without animal protein sources presented smaller activity. In conclusion, jundiás fed only soybean meal present reduction of alkaline proteases activity and lower growth. The combination of animal protein sources with soybean meal provides good development for jundiá juveniles.